(AUTO) EROTICISM OF MOURNING. THE INVENTION OF BORISAV STANKOVIĆ'S NARRATIVE PROCESS IN THE STORY THE DECEASED'S WIFE - Dubravka Bogutovac (Philological Studies, 2020)
The article analyzes the story of Borisav Stanković Decedent's Wife in the context of his novelist opus and opus in its entirety. Particular attention is paid to the narrative treatment of the subject of eroticism in relation to the context of the theme of death, characteristic of the entire Stanković's work. The narrator's position is considered, which has variable focalization, which tells the elements of modernity. The modernity of the story is expressed in its formal and content plan: the formal, readable fluency of the narrative voice, and the content, the opening of topics that have the status of the obscure.